ENHANCING WEBSITE USABILITY TESTING: CORRELATING EYE-TRACKING, GSR, AND SUS DATA WITH RESPECT TO GENDER PREFERENCES - Ali, Ismael A. (Science Journal of University of Zakho, 2024)
Having a professional team of web developers can produce a professional website, but cannot guarantee an expected usable website. This study presents a comprehensive multilayer approach for examining the correlations between different layers of user consciousness in website usability testing. It utilizes visual attention data from eye-tracking, emotional engagement data from galvanic skin response, and self-reporting data from the system usability scale. Testing AUK and UoZ university websites with 18 users using the Gazepoint GP3 system revealed insightful correlations among different layers of user consciousness, such as high emotional engagement is associated with higher fixation counts and shorter time-to-complete and thus lower SUS scores. Whereas low emotional engagement is associated with lower fixation counts, longer time-to-complete, and thus higher SUS scores. Gender preferences verifies the results from the literature on female users generally experiencing higher emotional arousal thus having lower time-to-complete and lower SUS scores. Design problems are presented in the form of improvement recommendations. The findings of the study highlight the importance of considering different layers of user consciousness in website usability testing, as well as the importance of gender preferences. Finally, current limitations and future works are presented.
Keywords: Website Usability Testing; Galvanic Skin Response; Eye-Tracking; System Usability Scale; Gender Differences